CGIAR Level Agricultural Results Interoperable System Architecture (CLARISA) factsheet - Ellul, Phillippe; Colomer, Jules; Abreu, David; Schuetz, Tonya; Tobon, Hector; Croft-Cusworth, Catriona (CGIAR Level Agricultural Results Interoperable System Architecture, 2020)
CLARISA is a web service that helps to transform raw data on CGIAR research and activities into meaningful information that can shape how we work, and reveal what our impacts are on development – on reducing poverty, improving food and nutrition security for health, and improving natural resources and ecosystem services.